Tinnitus reduction in patients with single-sided deafness: the effect of cochlear implantation, bone conduction devices, and contralateral routing of sound hearing aids investigated in a randomized controlled trial - Wendrich, Anne W.; Assouly, Kelly K. S.; van Heteren, Jan A. A.; Peters, Jeroen P. M.; Grolman, Wilko; Stokroos, Robert J.; Versnel, Huib; Smit, Adriana L. (Frontiers in Neurology, 2024)
Objectives Single-sided deafness (SSD) is often accompanied by tinnitus, resulting in a decreased quality of life. Currently, there is a lack of high level of evidence studies comparing different treatment options for SSD regarding tinnitus reduction. This randomized controlled trial (RCT) evaluated the effect of a cochlear implant (CI), bone conduction device (BCD), contralateral routing of sound (CROS), and no treatment on tinnitus outcomes in SSD patients, with follow-up extending to 24 months. Methods A total of 120 adult SSD patients were randomized to three groups: CI, a trial period with first a BCD on a headband, then a CROS, or vice versa. After the trial periods, patients opted for a BCD, CROS, or no treatment. At the start of follow-up, 28 patients were implanted with a CI, 25 patients with a BCD, 34 patients had a CROS, and 26 patients chose no treatment. The Tinnitus Handicap Inventory (THI), Tinnitus Questionnaire (TQ), the Visual Analog Scale (VAS), and the Hospital Anxiety and Depression Scale (HADS) were completed at baseline and at 3, 6, 12, and 24 months of follow-up. Results The CI and BCD groups showed significantly decreased tinnitus impact scores. The CI group showed the largest decrease, which was already observed at 3 months of follow-up. Compared to the baseline, the median THI score decreased by 23 points, the TQ score by 17 points, and the VAS score by 60 points at 24 months. In the BCD group, the TQ score decreased by 9 points, and the VAS decreased by 25 points at 24 months. The HADS anxiety and depression subscale showed no indication for anxiety or depression at baseline, nor at 24 months, for all groups. Conclusion In this RCT, SSD patients treated with a CI or BCD showed an overall decrease in tinnitus impact scores up to 24 months compared to baseline. The CI group reported a stable and the largest reduction. Cochlear implants appear to be superior to BCD and CROS, and no treatment for achieving partial or complete resolution of tinnitus in patients with SSD. Clinical trial registration Netherlands Trial Register, www.onderzoekmetmensen.nl/nl/trial/26952, NTR4457, CINGLE trial.